171 Early senior assessment and access to CT in an emergency department. Issue 12 (23rd November 2020) - Crespo, Marta de Andres; Zogg, Cheryl; Novak, Alex; Metcalfe, David
Abstract : Aims/Objectives/Background: The Rapid Assessment and Treatment (RAT) model provides early senior assessment of undifferentiated 'majors' patients and has been proposed as a strategy for improving Emergency Department (ED) efficiency. One goal of RAT is to organise essential imaging at an earlier stage within the patient's ED journey. This study aimed to identify any potential early impact of a RAT initiative on time to imaging for patients requiring CT head. Methods/Design: Electronic health record data were extracted for all patients that underwent head CT while in the ED over a 54-month period (48 months pre-intervention and 6 post-intervention) at a single Major Trauma Centre in England. Interrupted time series analysis was used to estimate any effect of RAT on time from ED arrival to imaging. Results/Conclusions: There was a pre-existing gradual trend over the entire time series towards patients waiting less time for CT. Although time to CT appeared to increase when the RAT model was implemented, this change was small and not statistically significant (9.8 [95% CI -1.6 to 21.3] minutes). Following RAT implementation, the pre-existing trend towards quicker access to CT resumed but without any change in the slope of the line. This early evaluation did not identify an association between RAT implementation and speed of access to CT head. The system may mature over time and further evaluations will be necessary to identify delayed effects on access to imaging as well as other process measures intended to improve ED safety and efficiency.